The satellite girl and milk cow [videorecording (DVD)] - Hyung-yun, Chang (Shout! Factory, 2018)
An out of commission satellite picks up a lovelorn ballad on her radio antenna and descents to earth to find the source of such sincere emotions. But on the way she is caught in a raging magical battle and transforms into Satellite Girl, complete with Astro Boy-like rocket shoes and weapon-firing limbs. Meanwhile, the balladeer in question, a loser twentysomething at a cafe open mic, meets the fate that befalls all broken-hearted lovers: he is turned into a farm animal.